Analisis pengendalian pencemaran air di zona hulu Sungai Citarum dengan model multi dimensional scalling - Iskandar A. Yusuf (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Citarum River is the largest river in West Java province, which due to high functionality and benefit of this river has been constructed three large cascade reservoirs: Saguling-Cirata-Jatiluhur that produce arround 1,900 MW electricity and irrigate the paddy fields with technical irrigation for DKI Jakarta over 240,000 ha and water supply through the West Tarum Canal, East Tarum Canal and North Tarum Canal.However, Citarum river is very polluted. Various efforts starting from laws and regulations as well as structuring of institution,and has been done several government programs establishing to control water pollution control. However, Citarum river can not be restorated properly due to disposal of wastewater still permits regardless of the factual condition. This study aimed at analysing the sustainability status of water pollution control in Citarum riverby applyingMulti Dimensional Scaling method covering the dimensions: Policy, Technical, Economic, Socio-Cultural, Law Enforcement and StakeholdersSupport, in order to define a proposal for him solution.The results of the study for the existing condition in 2015 that in all dimensions less sustainable.However, foryear 2030 and 2050 the so technical dimension increased significantly as a highly sustainable status followed by other dimensions achieving sustainable status. The analysis results indicated that a technical dimension can be more implemented than others, and the most difficult one is the economic dimension.